Improving fresh produce safety: application of UV tunnel technology and visual educational tools - Pokhrel, Sagar (My University, 2025)
Fresh produce is an important component of the human diet, and about 50% of the total fresh produce consumed in the US is domestically produced. Immigrants and refugees form a large part of the workforce in this industry, accounting for nearly 70% of all workers. Despite this reliance, most non-English-speaking growers struggle to learn and follow produce safety practices. This issue is further complicated due to a lack of relevant training materials tailored to different cultures and languages. To address this gap, visual educational materials for non-English-speaking growers were developed and evaluated in this study. A needs assessment with Iowa and Kansas refugee growers was conducted and involved feedback from extension personnel and community organizations. This assessment identified four critical areas of food safety knowledge: (1) workers’ health and sickness symptoms, (2) visitor management on produce farms, (3) contamination on produce farms through animals, and (4) appropriate application of Biological Soil Amendments of Animal Origins (BSAAOs). The ADDIE (Analysis, Design, Development, Implementation, and Evaluation) Design-Based Research framework was used to design four multilingual produce safety posters in Swahili, Burmese, Kirundi, and Nepali. The posters had animated, and culturally meaningful visuals based on the Produce Safety Rule. An evaluation was done with 26 growers using a pre-post-test design that relied on the Theory of Planned Behavior (TPB). All TPB constructs significantly improved after the poster intervention, with the largest gains observed in Perceived Behavioral Control (PBC) and intention, with statistically and practically significant improvements. The strong correlation between PBC, attitude, and intention demonstrated that posters had a strong positive effect on growers’ motivation to act, indicating that visual materials helped to improve produce safety awareness. In addition to the educational barriers, another critical issue in the fresh produce industry is the lack of an effective decontamination strategy for root vegetables, with reliance on traditional dip-washing using sanitizers. This results in a lack of effective decontamination due to organic load, surface texture, irregularities, and restrictions on using high concentrations of chemicals on fresh produce. These limitations can be overcome by the application of UV light or their combined application with effective chemical sanitizers. To address this gap, a study was conducted to determine the effectiveness of a novel decontamination tunnel system to reduce Escherichia coli contamination on whole carrots. The experiment used four groups: control, UV-C, Peracetic Acid (PAA), and combined treatment of UV-C and PAA, and was repeated in three trials. The study revealed that the highest mean microbial reduction (2.83 ± 0.10 log CFU/g) was found with the combination of PAA and UV-C, and this was significantly greater than PAA (2.38 ± 0.06 log CFU/g) and UV-C alone (1.49 ± 0.16 log CFU/g) (p < 0.0001). Such a complementary effect of UV-C and PAA illustrates superior effectiveness for root vegetable decontamination. By empowering underserved groups with culturally sensitive educational resources and by advancing decontamination strategies through innovative postharvest interventions, the scientific findings reported in this thesis work have practical relevance in ensuring improved microbial safety of fresh produce in the U.S.
Keywords: Fresh produce safety; Refugee growers; Produce safety posters; Carrots; Escherichia coli; Ultraviolet-C